JENIS DAN JUMLAH DALAM BAHASA ARAB DAN' PENERJEMAHANNY A KE DALAM BAHASA INDONESIA - AZIZI, IKHWAN (Al Qalam, 2010)
Translation from one language into another one basically always faces an abstacles of untransability factor. One of obstacles causing this case is grammatical factor. This paper discus such obstacles instrumen that has the concepts of types and number as one of Arabic grammatical instruments that has no comparison in lndonesia grammatical instruments. By taking the translation of the Qur'an as the data, the writer tries to know what startegy used by the translation team of Departement of Religious Affairs in overcoming this problem. Based on the data analysis, it is found that the translation team of Department of Religius Affair conducts three strategies to overcome this problem: using gramatical pattrens available in Indonesia language, substituting it with lexical unit, and giving special notes. Kaywords: Principals’ managerial roles, school-based management, teacher’s professional development activities, school improvement.